2018
DOI: 10.1007/s11071-017-4013-0
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic vibrations of flexible shallow axially symmetric shells

Abstract: In this work, chaotic dynamics of flexible spherical axially symmetric shallow shells subjected to sinusoidal transverse load is studied with emphasis put on the vibration modes. Chaos reliability is verified and validated by solving the implemented mathematical model by partial nonlinear equations governing the dynamics of flexible spherical shells and by estimating the signs of the largest Lyapunov exponents with the help of qualitatively different approaches. It is shown how the scenario of transition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Chaos widely exits in nature and man-made systems including those biological systems [20][21][22][23][24]. According to the famous Logistic map, it shows that the natural evolution of the population size could be chaotic.…”
Section: Introductionmentioning
confidence: 99%
“…Chaos widely exits in nature and man-made systems including those biological systems [20][21][22][23][24]. According to the famous Logistic map, it shows that the natural evolution of the population size could be chaotic.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that absolute and relative power are complementary indicators that may transmit significantly different brain function data [3]. The captured EEG data on brain activity allow applying methods of nonlinear dynamics to signals, as well as in other branches of modern science, such as mechanics [4,5], radiophysics [6], history [7], etc. Time-series entropy analysis is widely used in EEG studies.…”
Section: Introductionmentioning
confidence: 99%
“…In 1963, Lorenz [2] published a paper entitled "Decisive aperiodic flow" and performed a preliminary study on chaos by numerical simulations. Krysko et al [3] studied the chaotic dynamics of flexible spherical axially symmetric shallow shells subjected to a sinusoidal transverse load, solved the governing partial nonlinear equations, estimated the signs of the largest Lyapunov exponents, and verified the reliability of chaos. Kim et al [4] investigated the chaotic vibration of a rotor system with an asymmetric nonlinear stiffness and derived the motion equation of the rotor in a fixed coordinate system under Shilnikov chaotic vibration.…”
Section: Introductionmentioning
confidence: 99%